Peningkatan Kemampuan Pemahaman dan Representasi Matematis Siswa SMP Melalui Model Discovery Learning - rusydy rusydy (Universitas Syiah Kuala, 2019)
Abstract. This study aimed to determine the differences in the increase of understanding and mathematical representation skills of student learned using the discovery learning model and the conventional learning approaches. This research was an experimental research with pretest-posttest control design group. The instrument were the tests of mathematical understanding and representation skills. Data analysis involved N-Gain test, data distribution normality, data homogeneity test, ANOVA. The results showed that the increase in the understanding and mathematical representation skills of students learning using discovery learning models was better those using conventional learning approach. It was reviewed based on overall students and student grouping (high, medium, low). This study also concluded that there was no interaction between the learning model and student levels (high, medium, low) on increasing students' understanding and mathematical representation skills.Keywords: Understanding, mathematical representation skills, discovery learning learning model